"It's an Uncomfortable Subject"—a Qualitative Exploration of the Challenges and Potential Solutions to Depression Screening in Low Back Pain. - Sugrue, Julie; McKenna, Sean; MacHale, Siobhan; O'Sullivan, Kieran (PTJ: Physical Therapy & Rehabilitation Journal, 2026)
Importance Comorbid depression in people with low back pain (LBP) is associated with poorer prognosis. Objective The objective was to understand the challenges faced by musculoskeletal (MSK) triage physical therapists when screening for depression in LBP populations, and to generate actionable recommendations for overcoming these challenges. Design This study adopted a pragmatic hybrid descriptive qualitative approach, integrating elements of ethnography and action research. Setting Interviews were conducted in the Republic of Ireland and used purposive sampling of physical therapists working in MSK triage roles. Participants To be included, participants were required to have managed at least 1 person with LBP each week in the 3 months prior to recruitment. Intervention(s) or Exposure(s) The context explored was MSK triage physical therapists' experience with depression screening in people with LBP. Main Outcomes and Measure(s) The main outcomes were insights regarding challenges and potential solutions to depression screening. Semi-structured interviews were employed, with data analysis following a Reflexive Thematic Analysis framework. Results Fourteen MSK triage physical therapists participated. Challenges were organized into 3 themes: capacity (personal , professional , and system), culture (clinic , societal), and circuitous communication. Potential solutions were organized into 5 themes: training and education, standardized pathways, knowledge of and access to resources, screening tools, and normalizing depression screening in MSK triage equivalent to red flag screening. Conclusion The findings highlight capacity and cultural challenges that lead to circuitous communication. Addressing the potential solutions through implementation research could enhance depression screening practices by MSK triage physical therapists for people with LBP. Relevance This qualitative research offers novel insights into the challenges MSK triage physical therapists face when screening for depression in people with LBP. Importantly, it proposes actionable solutions with participants contributing as subject matter experts. Their pragmatic solutions can help facilitate consequential change and help normalize depression screening in MSK triage practice.